A Comparative Research on Civil Liability of Internet Service Providers Emphazising on U.S.A and European Legal System - amid Abhari; Hamid Miri (Faṣlnāmah-i Pizhūhish-i Huqūq-i Khuṣūṣī, 2012)
Internet Service Providers (ISPs) provide for their users a possible toaccess to internet and facilities on it. On the whole, we can talk aboutboth on the tort liability of ISPs for acts connecting with them andliability for user’s activities. The later is the most important andarguable subject about ISP liability. Contractual liability is alsoanother form of liability for ISPs. The liability in the first type is basedon fault. Thus, it must be cleared the creating elements of liability asincluding the fault element in order to establish that liability. In thesecond type of ISP tort liability the fault liability system is currentlyused and the reasons for those who say as opposite to it are notacceptable. Notwithstanding, ISPs are currently impunity of liabilityin U.S. and European Systems in which this impunity are applied asrule